Розробка алгоритма моніторингу стану водія за допомогою Аndroid-застосунку з метою підвищення рівня активної безпеки - Йовченко, А. В.; Шльончак, І. А.; Yovchenko, А.; Shlionchak, I. (ЦНТУ, 2023)
В статті виконано аналіз методів моніторингу небезпечного стану водія під час руху транспортного засобу. Наведено перелік програм, які використовуються при цьому. Для проведення досліджень було обрано мобільний додаток Drive Safely, в основу роботи якого покладено моніторинг стану очей та роту водія. Згідно проведених досліджень PERCLOS очей не повинен перевищувати 28 %, а PERCLOS роту не повинен перевищувати 30 %. Розроблено алгоритм розпізнавання аварійних ситуацій у кабіні транспортного засобу на основі зображення очей та роту водія із фронтальної камери смартфону. The purpose of the research is the analysis of existing systems for monitoring the driver's condition using an Android mobile application to increase the level of active safety with the development of an algorithm for monitoring the driver's condition. At the same time, such parameters as turns and tilts of the head, duration of eyelid blinking, yawning are taken into account. As a result, the state of drowsiness, impaired attention, and drunkenness of the driver is analyzed. The article analyzes the methods of monitoring the dangerous condition of the driver during the movement of the vehicle. The list of programs used in this case is given. The Drive Safely mobile application was chosen for the research, which is based on monitoring the condition of the driver's eyes and mouth. Based on research, eye PERCLOS should not exceed 28% and mouth PERCLOS should not exceed 30%. An algorithm for recognizing emergency situations in the vehicle cabin based on the image of the driver's eyes and mouth from the front camera of a smartphone has been developed. As a result of the analysis of existing Android applications, an algorithm for recognizing emergency situations in the cabin of the vehicle was developed. The algorithm was obtained based on the image of the smartphone's front camera. This algorithm takes into account all possible dangerous conditions of the driver behind the wheel of the vehicle. As a result of the conducted research, an analysis of the existing systems for monitoring the driver's condition using the Drive Safely mobile Android application was carried out. As a result of the analysis of existing Android applications, an algorithm for recognizing emergency situations in the cabin of the vehicle was developed. The use of this algorithm in the program and the connection of its results to the cloud environment will allow it to self-improve and increase the efficiency of its operation, thus increasing the level of active security.
Development of an Algorithm for Monitoring the Driver's Condition Using an Android Application in Order to Increase the Level of Active Safety
Keywords: моніторинг; небезпечний стан; водій; активна безпека; аварійні ситуації; смартфон; транспортний засіб; monitoring; dangerous condition; driver; active safety; emergency situations; smartphone; vehicle